Mycobacterium tuberculosis of the temporal bone. Issue 1 (1st January 2021) - Friedland, Yael; Whitmore, Timothy; Chu, Eric; Kuthubutheen, Jafri
Abstract: Tuberculous otitis media (TOM) is a rare manifestation of tuberculosis (TB) caused by Mycobacterium tuberculosis . A case of a 64-year-old female and challenges involved in arriving at the diagnosis of TOM is presented. The patient had surgery for suspected complicated cholesteatoma, but given intraoperative findings and clinical suspicion, investigations were performed to exclude multiple differential diagnoses, including TOM. Initial histopathological finding showing necrotising granulomata was suspicious for TB, but initial samples were culture negative. However, in the absence of alternative diagnoses and high pre-test probability the patient was commenced on empirical treatment. During therapy, a sample of ear cerumen was sent for mycobacterial culture and was found to be culture positive for M. tuberculosis, confirming the diagnosis. To our knowledge, this is the first case to report M. tuberculosis cultured from ear cerumen. The patient is being treated with six months of therapy and is showing improvement with resolution of symptoms.